Genomic Assays for Identification of Chikungunya Virus in Blood Donors, Puerto Rico, 2014 - Chiu, Charles Y. (Emerg Infect Dis, 2015)
A newly developed transcription-mediated amplification assay was used to detect chikungunya virus infection in 3 of 557 asymptomatic donors (0.54%) from Puerto Rico during the 2014–2015 Caribbean epidemic. Viral detection was confirmed by using PCR, microarray, and next-generation sequencing. Molecular clock analysis dated the emergence of the Puerto Rico strains to early 2013.